2022
DOI: 10.1186/s12894-022-01005-8
|View full text |Cite
|
Sign up to set email alerts
|

The Paris System for reporting urinary cytology improves the negative predictive value of high-grade urothelial carcinoma

Abstract: Background The Paris System (TPS) for reporting urinary cytology differs from conventional systems (CS) in that it focuses on the diagnosis of high-grade urothelial carcinoma (HGUC). This study investigated the impact of TPS implementation on the diagnostic accuracy of HGUC by comparing it with our institutional CS. Methods A total of 649 patients who underwent transurethral resection of bladder tumor (TURBT) between January 2009 and December 2020 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Studies conducted by Goutas et al 20 . and Yamazaki et al 21 . both reported ROHM of 95% and 97.8%, respectively 20,21 …”
Section: Discussionmentioning
confidence: 96%
“…Studies conducted by Goutas et al 20 . and Yamazaki et al 21 . both reported ROHM of 95% and 97.8%, respectively 20,21 …”
Section: Discussionmentioning
confidence: 96%
“…Clinically, as low grade UC has low malignant potential while high grade UC carries risk of disease progression, metastases and cause mortality, it is very important not to overlook high grade UC cases in particular [31][32][33]. Thus, there is a push to focus on diagnosing predominantly high grade UC in The Paris System [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…22,43 Although urine cytology is highly accurate for detecting HGUC, its sensitivity remains relatively low, even with TPS. 44,45 Thus, the presence of a predictive marker for HGUC, in addition to urine cytology, might be helpful in daily practice. The present study and Hinsch et al (2017) showed that the TUBB3 expression was significantly associated with HGUC.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, since HGUC can invade and cause death, there is a push to focus on diagnosing HGUC in TPS for urine cytology 22,43 . Although urine cytology is highly accurate for detecting HGUC, its sensitivity remains relatively low, even with TPS 44,45 . Thus, the presence of a predictive marker for HGUC, in addition to urine cytology, might be helpful in daily practice.…”
Section: Discussionmentioning
confidence: 99%